Respiratory Bacterial Culture Sampling in Expectorating and Non-expectorating Patients With Cystic Fibrosis - Eyns, Hanneke; Piérard, Denis; De Wachter, Elke; Eeckhout, Leo; Vaes, Peter; Malfroot, Anne (Frontiers in Pediatrics, 2018)
Purpose: Different respiratory sampling methods exist to identify lower airway pathogens in patients with cystic fibrosis (CF), of which bronchoalveolar lavage (BAL), and expectorated sputum are considered the “gold standard.” Because BAL cannot be repeated limitless, the diagnosis of lower respiratory tract infections in non-expectorating patients is challenging. Other sampling techniques are nasal swab, cough swab, and induced sputum. The purpose of this study (NCT02363764) was to compare concordance between the microbiological yield of nasal swab, cough swab, and expectorated sputum in expectorating patients; nasal swab, cough swab, and induced sputum in non-expectorating patients; nasal swab, cough swab, induced sputum, and BAL in patients requiring bronchoscopy (“BAL-group”); and to determine the clinical value of cough swab in non-expectorating patients with CF. Methods: Microbiological yield detected by these different sampling techniques was compared between and within 105 expectorating patients, 30 non-expectorating patients and BAL-group (n = 39) in a single CF clinic. Specificity, sensitivity, positive (PPV), and negative (NPV) predictive values were calculated. Results: Overall low sensitivity (6.3–58.0%) and wide-ranging predictive values (0.0–100.0%) indicated that nasal swab was not appropriate to detect lower airway pathogens [Pseudomonas aeruginosa (Pa), Staphylococcus aureus (Sa), and Haemophilus influenzae (Hi)] in all three patient groups. Microbiological yield, specificity, sensitivity, PPV, and NPV of cough swab and induced sputum were largely similar in non-expectorating patients and in BAL-group (except sensitivity (0.0%) of induced sputum for Hi in BAL-group). Calculations for Pa and Hi could not be performed for non-expectorating patients because of low prevalence (n = 2 and n = 3, respectively). In expectorating patients, concordance was found between cough swab and expectorated sputum, except for Hi (sensitivity of 40.0%). Conclusion: Our findings suggest that cough swab might be helpful in detecting the presence of some typical CF pathogens in the lower airways of clinically stable patients with CF. However, in symptomatic patients, who are unable to expectorate and who have a negative cough swab and induced sample, BAL should be performed as it currently remains the “gold standard.”